2020
DOI: 10.4209/aaqr.2019.12.0660
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Behavior of PCDD/Fs Congeners by Addition of N-containing Compound in the Iron Ore Sintering

Abstract: PCDD/Fs are typical toxic persistent aromatic compounds that greatly reduce air quality and harm human health. In this study, urea's suppressive effect on PCDD/Fs and their congener emissions was investigated via sintering pot tests, and the inhibition mechanisms were studied. The results showed that the I-TEQ values for the total PCDD/Fs decreased from 0.50 to 0.20, 0.12 and 0.20 ng I-TEQ Nm-3 after adding solid 0.02, 0.035 and 0.05 wt.% urea particles, respectively, to the iron ore sintering mixture, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…PCDDs, PCDFs, and PCBs are classified as persistent organic pollutants (POPs) due to their toxicity, carcinogenicity and persistence in the human body (Anezaki et al, 2021). Among them, polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) are collectively known as PCDD/Fs (Wang et al, 2020). They have been identified as pollutants and are present in almost every component of the global ecosystem, including air, aquatic and marine sediments, fish, wildlife, and human adipose tissue and blood (Goldman et al, 1989;Safe et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…PCDDs, PCDFs, and PCBs are classified as persistent organic pollutants (POPs) due to their toxicity, carcinogenicity and persistence in the human body (Anezaki et al, 2021). Among them, polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) are collectively known as PCDD/Fs (Wang et al, 2020). They have been identified as pollutants and are present in almost every component of the global ecosystem, including air, aquatic and marine sediments, fish, wildlife, and human adipose tissue and blood (Goldman et al, 1989;Safe et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CaO was discovered to facilitate OCDD/TCDD generated from PCP prominently at 850 • C by Lu et al [30]. In FG3 and FG4, the increase in CaO or CaCO3 reduced the fraction of HpCDD and HxCDD, but slightly increased the mass proportion of low-chlorinated PCDDs, which might be a result of the mutual chlorination of dioxins that was inhibited [26]. Among them, the fraction of HpCDD reduced from 34% to 27%, 31%, 26%, and 23% and HxCDD declined from 21% to 17%, 14%, 16%, and 15%, while PeCDD increased from 5% to 7%, 7%, 7%, and 10% and TCDD increased from 1% to 2%, 3%, 2%, and 2%.…”
Section: Effects On Pcdd/fs Congenersmentioning
confidence: 90%
“…Nitrogen-based, sulfur-based, and alkali-based are three common inhibitors in some current studies. The sulfur-based inhibitors will increase sulfur oxides such as SO 2 emission in flue gas, and consequently increase the desulfuration burden for the iron and steel industry [25,26]. The mechanism and effect of nitrogen-containing inhibitors, especially urea, added into the iron ore sintering raw mix has already been investigated and verified by many researchers [27,28].…”
Section: Introductionmentioning
confidence: 98%
“…8 Moreover, studies have shown that solid fuels mainly release chlorine in the form of HCl under high temperature conditions 9 , but in the presence of O 2 , they can be converted into Cl 2 through the Deacon reaction 10 , and the activity of Cl 2 is much higher than that of HCl. 7 Yifan Wang et al 11 studied the inhibitory effect of urea on PCDD/Fs using a sintered tank and analyzed its possible dechlorination inhibitory mechanism. It was found that the toxic equivalent of urea was greatly reduced by mixing urea particles, indicating that urea has the effect of inhibiting chlorination and enhancing dechlorination.…”
Section: Introductionmentioning
confidence: 99%